Fossilization: A Case Study of Three Indonesian Adults Living in English-Speaking Countries - Santosa, Bernadette (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2025)
Researches have proved that fossilization happens to every second-language learner. What varies is the degrees of fossilization and what causes it to happen. In her research, Ene (2006) mentions that advanced English language learners exhibit inconsistentuse of tenses, inaccurate use of prepositions, articles, etc. This research finds similar things. Articles, tenses and prepositions are grammatical aspects which are fossilized. In addition to finding out which grammatical aspects are fossilized, this research also tries to find out factors which contribute to the participants’ fossilization. Influence of their first language is one of the factors. Surprisingly however, based on the feedback from two English native speakers, there is an issue of natural use of the English language. This is surprising since the participants have been living in those English-speaking countries for more than a decade. What is more, there is one factor which leads to fossilization but is not found in the previous study nor in other researches